Measuring the Benefits of the Development Strategy of the “21st Century Maritime Silk Road” via an Intervention Analysis Approach: Evidence from China and Neighbouring Countries in Southeast Asia - Xuejun, Jiang; Yingzi, Fu (Panoeconomicus, 2018)
The present study adopts a new political intervention analysis approach to evaluate the impact of the “21st Century Maritime Silk Road” (MSR) policy. The basic concept is to investigate dependence amongst cross-sectional units to construct counterfactuals without intervention. Thus, the effect of policy intervention is simply the difference between the outcomes with and without intervention. The panel data of 14 countries along MSR are used to illustrate the methodology. Real data analysis shows that the MSR policy exerts a positive effect on the trade of China and Southeast Asian countries. Furthermore, policy implications are provided based on the analysis.Key words: Political intervention analysis, Panel data, Time series, Factor analysis model.JEL: C13, C33, E65, F17.Merenje koristi strategije razvoja “pomorskog puta svile 21. veka” putem pristupa analize intervencija: Dokazi iz Kine i susednih zemalja u jugoistočnoj AzijiIstraživanje koristi novi pristup analize političkih intervencija kako bi procenio uticaj politike “pomorskog puta svile 21. veka” (MSR). Osnovna koncepcija je da se prouči zavisnosti među presečnim jedinicama radi konstruisanja stanja bez intervencije. Stoga je efekat politike intervencije jednostavno razlika između rezultata sa i bez intervencije. Podaci panela sa 14 zemalja uz MSR su koriščena za ilustraciju metodologije. Analiza realnih podataka pokazuje da politika MSR pozitivno utiče na trgovinu Kine i jugoistočne Azije. Pored toga, na osnovu analize date su implikacije rezultata na politiku.Ključne reči: Analiza političkih intervencija, podaci panela, vremenske serije, model faktorske analize.